Dr. Cassandra Mark-Thiesen and Dr. Noemi Alfieri on anti-colonial networks in African literature - Mark-Thiesen, Cassandra; Alfieri, Noemi (Cluster Conversations, 2023)
Cluster fellow Dr. Noemi Alfieri talks with her host and Junior Research Group Leader Dr. Cassandra Mark-Thiesen about her latest research project "Mapping anti-colonial networks through literature. Transnational connections of African thinkers in the reconfiguration of space and thought (1950s - 70s)"